Peculiarities of adolescents and youth socialization in the context of formal and informal education - Sazonenko, H.; Korch, V. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article describes features of educational socialization of teenagers and young men in a context of formal and informal education, with account of the Ukrainian Humanitarian Lyceum at Taras Shevchenko National University of Kyiv, and analyses empirical research results of a psychological, social and spiritual maturity of pupils in this lyceum.